Evaluation of Patients with Exploratory Laparotomy for Acute Abdomen with Intraoperative Finding of Acute Pancreatitis - Akram Abed , Bashar; Jameel Kareem , Duraid; Saleh Ibrahim , Nazar (Diyala Journal of Medicine, 2022)
Background: Acute pancreatitis (AP) is one of the main causes of acute abdomen that requires hospitalization and multidisciplinary management. The spectrum of the disease is wide with variable presentations that mimic the clinical features of other acute illnesses. Occasionally the diagnosis of AP is only made at laparotomy, especially when there is doubt in the preoperative diagnosis. Objective: To evaluate the findings during exploratory laparotomy for patients with acute abdomen and were diagnosed as cases of AP intraoperatively, and to determine the postoperative outcome during the follow up period for these patients. Patients and Methods: A retospective study performed at the Department of General Surgery- Baquba Teaching Hospital- Diyala- Iraq, from January 2011 to December 2020. Thirty-three patients (16 male and 17 female) were included, all patients had history of acute abdomen with unknown cause preoperatively, in spite of doing the available preoperative investigations, and were found to have acute pancreatitis intraoperatively. A standardized data collection form was completed and analyzed for each patient. Results: The patients' ages ranged from 8 to 75 years with a mean age of 40.2 years. The majority of the patients were found to have pancreatic oedema (66.67%), followed by hemorrahgic pancreatitis (15.15%), pancreatic necrosis (12.12%) and pancreatic tumours that presented as acute pancreatitis (6.06%). During the follow up period 13 patients (39.39%) recovered with no complications while 20 patients (60.6%) developed one or more complication mainly surgical site infections in 18.18% of patients, pancreatic pseudocyst (15.15%), death (15.15%), ascites (9.1%), chronic pancreatitis (6.1%), pleural effusion (6.1%), while ileus, ARDS, DIC and acute renal failure occurred in (3%) for each. Conclusion: AP is an important cause of acute abdomen that is associated with severe mortality and morbidity and a high index of suspicion is needed to avoid the frequent misdiagnosis. Despite of rapid advances in the diagnostic strategy, still exploratory laparotomy is indicated in some cases to reach a sound diagnosis although such intervention is undesirable and might increase the postoperative morbidity and mortality.